Kristologi Pangala Tondok: Dialektika Kepemimpinan Kristen dalam Konteks Multireligius di Toraja - Frans Paillin Rumbi (Societas Dei: Jurnal Agama dan Masyarakat, 2025)
Discussion about Pangala Tondok Christology began when the Torajan Church decided on Tongkonan Sangullele terms for cultural and religious identity. This study aims to foster fruitful discussion regarding Pangala Tondok Christology in Toraja's multireligious setting (interdenominational church and interreligious). Library research is used in this study, and I created a synthesis model based on Stephen B. Bevans. The first outcome is that Jesus Christ can be portrayed as a new Pangala Tondok in an interdenominational church. The Tongkonan offspring descended from him. The Torajan Church promotes an inclusive, modest, amiable, and transparent approach to interreligious discourse, embracing a respectful attitude toward other religions.